Structures for Nuclear Facilities Analysis, Design, and Construction - Bangash, M.Y.H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book provides a general introduction to the topic of buildings for resistance to the effects of abnormal loadings. The structural design requirements for nuclear facilities are very unique. In no other structural system are extreme loads such as tornadoes, missile and louds-interaction, earthquake effects typical in excess of any recorded historical data at a site, and postulated system accident at very low probability range explicitly, considered in design. Many design anaysis are included with examples. It covers the whole spectrum of extreme load which has to be considered in the structural design of nuclear facilities and reactor buildings, the safety criteria, the structural design, the analysis of containment. Test case studies are given in a comprehensive treatment. Computer program solutions supporting analysis are given in the appendices. Each major section contains a full explanation which allows the book to be used by students and practicing engineers, particularly those facing formidable task of having to design complicated building structures with unusual boundary conditions.
Introduction -- Load and Behaviour Criteria -- Structural Design and Analysis -- Seismic Analysis and Design -- Design against Impulse and Impact Loads -- Experimental.
Keywords: Engineering; Materials; Mechanical engineering; Civil engineering; Engineering; Structural Mechanics; Civil Engineering; Continuum Mechanics and Mechanics of Materials; Building Construction